Some problems on the slope handling in the highway construction in China - Huang, Dong; Wei, Zuoan; Chen, Yulong; Muhammad, Irfan (Penerbit Universiti Kebangsaan Malaysia, 2017)
In western China, with plenty of transportation infrastructures being constructed, many man-made slopes have been formed in the highway constructions along the highway routes. Fortunately, most of these man-made slopes were in middle or small scales. However, in the procedure of slope design as well as potential landslides controlling, there are many problems and error viewpoints, such as slope angle is determined mainly on the basis of designers’ experience without considering the lifetime of control projects, calculating slope satiability and optionally choosing remedial measurements. If not well resolved, these problems will affect not only the safety of highway operation, but also project investment. Based on the experiences in the highway engineering, these problems have been summarized in detailed and discussed in this paper. Some advices have also been put forward, which could be beneficial to the highway construction and operation.